2018
DOI: 10.1016/j.vaccine.2018.01.087
|View full text |Cite
|
Sign up to set email alerts
|

Immune parameters to p67C antigen adjuvanted with ISA206VG correlate with protection against East Coast fever

Abstract: HighlightsThree doses of p67C antigen generated stronger immune responses than two doses.Antibody titers and CD4+ T-cell proliferation correlated with protection against ECF.The number of doses could not be reduced from three to two without compromising the protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…This is in line with a previous study in mice, which used Ad5/MERS and boosted with spike protein nanoparticles and they found that balanced Ab and cell-mediated responses were generated (56). Importantly, in the current study, upon challenge, ∼53% of the cattle were immune to an approximately LD 93 sporozoite challenge, which is the highest challenge dose used to test p67C protective capacity and using more than three times less p67C Ag to date (7,10,11). ECF is a dose-dependent disease and the animals in the challenge experiment got double the amount of sporozoites compared with any of the previous published experiments (7,10,11), the immune response generated specifically against p67C had to fight a significantly higher parasite load to get 53% of the animals protected.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in line with a previous study in mice, which used Ad5/MERS and boosted with spike protein nanoparticles and they found that balanced Ab and cell-mediated responses were generated (56). Importantly, in the current study, upon challenge, ∼53% of the cattle were immune to an approximately LD 93 sporozoite challenge, which is the highest challenge dose used to test p67C protective capacity and using more than three times less p67C Ag to date (7,10,11). ECF is a dose-dependent disease and the animals in the challenge experiment got double the amount of sporozoites compared with any of the previous published experiments (7,10,11), the immune response generated specifically against p67C had to fight a significantly higher parasite load to get 53% of the animals protected.…”
Section: Discussionsupporting
confidence: 90%
“…Twenty-one days after the last boost, all animals were given an s.c. syringe challenge of 1 ml of T. parva Muguga sporozoites (stabilate no. 3087), as previously described ( 11 ). After the challenge, all experimental cattle were monitored daily for changes in rectal temperatures and other clinical manifestations of ECF, and the ECF scores were calculated (Rowland index) ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination of cattle using a subunit vaccine based on the recombinant versions of p67 demonstrated a reduction in disease incidence by approximately 70% in the laboratory [30,31] and about 30% under field tick challenge [32]. Recent attempts have been made to improve the vaccination regimen by modifying the antigen preparation, dosage or adjuvant systems [33].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination of cattle using a subunit vaccine based on the recombinant versions of p67 demonstrated a reduction in disease incidence by approximately 70% in the laboratory (29, 30) and about 30% under field tick challenge (31). Recent attempts have been made to improve the vaccination regimen by modifying the antigen preparation, dosage or adjuvant systems (32).…”
Section: Introductionmentioning
confidence: 99%